Ngajiblox Hyperreality: a Netnographic Study of Simulacra in Virtual Qur’anic Study Practices by Majelis Roblox Indonesia on the Roblox Platform - Rifdah Fadhillah; Diah Ariani Arimbi; Johny Alfian Khusyairi (JURNAL PENELITIAN, 2026)
This study examines Ngajiblox, a virtual Qur’anic study initiative organized by Mario (Majelis Roblox Indonesia) on the Roblox platform, to analyze how digital environments produce religious simulacra and hyperreal experiences. As religious practices increasingly move online, the research explores how Islamic learning, ethical conduct, and communal interaction are reconfigured in virtual space. A descriptive qualitative method with a netnographic approach was employed. Data were gathered through online observation, in-depth interviews, and content analysis, and interpreted using Jean Baudrillard’s theory of simulacra and simulation. The findings reveal that the virtual mosque functions as a socio-religious arena where Islamic practices are reconstructed through digital symbols, avatars, spatial design, and virtual artifacts. Rather than simply imitating offline gatherings, the sessions generate an autonomous religious reality in which learning and spirituality are experienced as authentic. Elements such as mosque icons, gender-segregated areas, and live broadcasts from a physical mosque in Klaten strengthen the sense of hyperreal religiosity. Participants engage in study, ethical reflection, and social interaction in ways that parallel offline life, while remaining aware of limitations such as distraction and “instant” spirituality. Islamic subjectivity thus emerges through negotiation between digital simulation and embodied faith.